Aquatic weeds as the next generation feedstock for sustainable bioenergy production. (March 2018) - Kaur, Manpreet; Kumar, Manoj; Sachdeva, Sarita; Puri, S.K.
Graphical abstract: Highlights: High yield and unique composition makes aquatic weeds a potential energy resource. Ability to grow in wastewater makes them an economical bioenergy feedstock. Utilization of aquatic weeds for energy production controls the ecological damage. Production & conversion of aquatic weeds couple energy generation with bioremediation. Abstract: Increasing oil prices and depletion of existing fossil fuel reserves, combined with the continuous rise in greenhouse gas emissions, have fostered the need to explore and develop new renewable bioenergy feedstocks that do not require arable land and freshwater resources. In this regard, prolific biomass growth of invasive aquatic weeds in wastewater has gained much attention in recent years in utilizing them as a potential feedstock for bioenergy production. Aquatic weeds have an exceptionally higher reproduction rates and are rich in cellulose and hemicellulose with a very low lignin content that makes them an efficient next generation biofuel crop. Considering their potential as an effective phytoremediators, this review presents a model of integrated aquatic biomass production, phytoremediation and bioenergy generation to reduce the land, fresh water and fertilizer usage for sustainable and economical bioenergy.